Expert Elicitation for Latent Growth Curve Models: The Case of Posttraumatic Stress Symptoms Development in Children With Burn Injuries - Veen, Duco; Egberts, Marthe R.; van Loey, Nancy E. E.; van de Schoot, Rens (Frontiers in Psychology, 2020)
Experts provide an alternative source of information to classical data collection methods such as surveys. They can provide additional insight into problems, supplement existing data or provide insights when classical data collection is troublesome. In this paper we explore the (dis)similarities between expert judgements and data collected by traditional data collection methods regarding the development of Posttraumatic Stress Symptoms (PTSS) in children with burn injuries. By means of an elicitation procedure, the experts’ domain expertise is formalized and represented in the form of probability distributions. The method is used to obtain beliefs from 14 experts, including nurses and psychologists. Those beliefs are contrasted with questionnaire data collected by Egberts, van de Schoot, Geenen, & van Loey (2018) on the same issue. The individual and aggregated expert judgements are contrasted with the questionnaire data by means of Kullback-Leibler divergences. The aggregated judgements of the group that mainly includes psychologists resembles the questionnaire data more than almost all of the individual expert judgements.